SANKSI ATAS NASABAH (MURABAHAH) MAMPU YANG MENUNDA-NUNDA PEMBAYARAN HUTANG (Studi Fatwa DSN) - Hayati, Suci (JURNAL TAPIS, 2012)
AbstractEstablishing financial institutions based on sharia law aims to apply Islamic economic values in society. Existence of Islamic banks is to develop the principles of sharia, especially for the models imposed a business as if the debtor fails to perform its obligation to repay the debt on time while he has the ability, so he will be punished because of it. Therefore, national Islamic council set fatwa delay penalties to customers postpone payments. The appearing problem is that the sanctions that DSN set fully benefit Islamic banks? The goal to be achieved is to determine whether the sanctions that DSN set fully benefit Islamic banks. After researching DSN provision that sanctions fines is tied to a social fund which al qardhul hasan, while there are losses incurred by the Islamic banks in the amount of fee billing process that should be charged to the customer.Keywords: Sanctions, cutomer, murabahah, debt.